OP0209-HPR Incidence of first cardiovascular event in spanish patients with chronic inflammatory rheumatic diseases: prospective data from the carma project. (15th June 2017) - Martinez, MA Martin; Castañeda, S; Gonzalez-Juanatey, C; Sanchez-Alonso, F; Barril, S Marsal; Romera-Baures, M; Santos-Rey, J; Pinto-Tasende, JA; Tornero-Molina, J; Lopez-Gonzalez, R; Sanchez-Gonzalez, MD; Llorca, J; et al.
Abstract : Objectives: To determine the incidence and risk factors implicated in the development of first cardiovascular event (CVE) in patients with chronic inflammatory rheumatic diseases (CIRD) attending rheumatology clinics after 2.5 years of follow-up. Methods: Analysis of data after 2.5 years of follow-up in an observational prospective study [CARdiovascular in rheuMAtology (CARMA) project] that includes a cohort of patients with CIRD [rheumatoid arthritis (RA), ankylosing spondylitis (AS), and psoriatic arthritis (PsA)] and another cohort of matched individuals without CIRD attending outpatient rheumatology clinics from 67 hospitals in Spain. The cumulative incidence per 1000 patients and the incidence density per 1000 patient-months of non-fatal CVE were estimated in both cohorts at 2.5 years from the start of the project. Weibull proportional hazard model was used to calculate the Hazard Ratio (HR) and 95% confidence interval (95% CI) of the risk factors involved in the development of CVD events. Losses to follow-up and their causes were also analyzed. Results: The total number patient who completed the follow-up visit at 2.5 years was 2, 598 (89.2% of those who started the study). Seven patients had died due to CVE and 23 because of non-CVE. The higher number of losses to follow-up was found in the control group (15.81%), because many of them were not periodically follow-up at the outpatient clinics. Cardiovascular cumulative incidence in patients with CIRD 15.30 cases per 1000 patients (95% CI: 12.93–17.67), being higher in AS patients 22.03 (95% CI: 11.01–33.04). The higher risk of developing a first CVE during the 2.5 years of follow-up was in patients with AS (HR: 4.11, 95% CI: 1.07–15.79; p: 0.04), those with older age (HR:1.09; 95% CI: 1.05–1.13, p<0.001), higher systolic blood pressure (HR: 1.02; 95% CI: 1.00–1.04, p=0, 01) and longer duration of the rheumatic disease (HR: 1.07; 95% CI: 1.03–1.12), p<0.01). In contrast, woman gender was a protective factor (HR: 0.43; 95% CI: 0.18–1.00, p=0.05). Conclusions: Patients with AS prospectively followed-up at rheumatology outpatients clinics show higher risk of developing a first CVE than those with RA or PsA. Besides traditional CVD risk factors a longer time course of the disease is a risk factor for the development of CVD in patients with CIRD. Acknowledgements: This project has been supported by an unrestricted grant from Abbvie, Spain. The design, analysis, interpretation of results and preparation of the manuscript has been done independently of Abbvie. Disclosure of Interest: None declared